2015
DOI: 10.1007/s10964-015-0300-6
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Reciprocal Relationships Between Discrimination and Ethnic Affect or Depressive Symptoms Among Chinese American Adolescents

Abstract: Discrimination plays an important role in the development of ethnic minority adolescents. However, previous studies have often adopted a unidirectional model examining the influence of discrimination on adolescent development, thus leaving the potential reciprocal relationship between them understudied. Moreover, there is a dearth of studies on Chinese Americans in the discrimination literature. Therefore, this study aimed to examine the reciprocal relationships between discrimination and two measures of adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 58 publications
6
41
0
Order By: Relevance
“…However, in the lagged analyses, findings suggested that when Mexican‐origin adolescent mothers experienced increases in perceived discrimination (relative to their own average experiences), they reported decreases in ERI affirmation 1 year later. These findings are consistent with some previous empirical work indicating that adolescents’ positive sense of self suffers in the face of perceived discrimination (e.g., Hou et al., ; Seaton et al., ; Umaña‐Taylor & Guimond, ) but inconsistent with one study that reported no association between WP changes in discrimination and Latino and African American adolescents’ affirmation (Pahl & Way, ). Furthermore, findings are somewhat inconsistent with theoretical models that emphasize that discrimination may evoke coping resources (PVEST) and a greater awareness of self (rejection–identification model).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, in the lagged analyses, findings suggested that when Mexican‐origin adolescent mothers experienced increases in perceived discrimination (relative to their own average experiences), they reported decreases in ERI affirmation 1 year later. These findings are consistent with some previous empirical work indicating that adolescents’ positive sense of self suffers in the face of perceived discrimination (e.g., Hou et al., ; Seaton et al., ; Umaña‐Taylor & Guimond, ) but inconsistent with one study that reported no association between WP changes in discrimination and Latino and African American adolescents’ affirmation (Pahl & Way, ). Furthermore, findings are somewhat inconsistent with theoretical models that emphasize that discrimination may evoke coping resources (PVEST) and a greater awareness of self (rejection–identification model).…”
Section: Discussionsupporting
confidence: 86%
“…Likewise, Seaton and colleagues tested an alternate model in which positive ethnic–racial affect not only predicted subsequent discrimination among a sample of African Americans but also found that this directionality was not supported (Seaton et al., ). Finally, Hou, Kim, Wang, Shen, and Orozco‐Lapray () found that perceived discrimination not only predicted positive ethnic–racial affect in early adolescence but also found that positive ethnic–racial affect negatively predicted discrimination in middle adolescence among a sample of Chinese Americans.…”
Section: Theoretical Framework Linking Discrimination and Erimentioning
confidence: 99%
“…Longitudinal studies during adolescence found an association between increasing frequencies of racism and worse mental health [85]; these studies also found that perceiving being stereotyped as a perpetual foreigner led to increasing perceived discrimination, which in turn led to increased risk of depression over time [37]. Studies of adolescents over time also found that not only may discrimination influence depression, but there may be a feedback loop whereby depression also influences future perceptions of discrimination [35]. …”
Section: Resultsmentioning
confidence: 99%
“…This study found that while there has been significant improvement for Māori youth over the 2001–2012 time period, they are disproportionately exposed to socioeconomic adversity compared to European students, and the impact of socioeconomic disadvantage for Māori carries more significant health burdens. Exposure to poverty is particularly damaging during the adolescence period, 39,40 particularly when coupled with discrimination 41,42 . Obligations under Te Tiriti o Waitangi, the founding document of Indigenous and settler governance in New Zealand, is testament to our ancestors’ aspirations for bicultural partnership.…”
Section: Discussionmentioning
confidence: 99%